The Contribution of Autoantibodies to Inflammatory Cardiovascular Pathology - Meier, Lee A.; Binstadt, Bryce A. (Frontiers in Immunology, 2018)
Chronic inflammation and resulting tissue damage underlie the vast majority of acquired cardiovascular diseases (CVD), a general term encompassing a widely diverse array of conditions. Both innate and adaptive immune mechanisms contribute to chronic inflammation in CVD. Although maladies such as atherosclerosis and cardiac fibrosis are commonly conceptualized as disorders of inflammation, the cellular and molecular mechanisms that promote inflammation during the natural history of these diseases in human patients are not fully defined. Autoantibodies (AAbs) with specificity to self-derived epitopes accompany many forms of CVD in humans. Both adaptive/induced auto-antibodies (iAAbs, generated following cognate antigen encounter) and also autoantigen-reactive natural antibodies (NAb, produced independently of infection and in the absence of T cell help) have been demonstrated to modulate the natural history of multiple forms of CVD including atherosclerosis (ASCVD), dilated cardiomyopathy (DCM), and valvular heart disease (VHD). Despite the breadth of experimental evidence for the role of AAbs in CVD, there is a lack of consensus regarding their specific functions, primarily due to disparate conclusions reached, even when similar approaches and experimental models are used. In this review, we seek to summarize the current understanding of AAb function in CVD through critical assessment of the clinical and experimental evidence in this field. We additionally highlight the difficulty in translating observations made in animal models to human physiology and disease and provide a summary of unresolved questions that are critical to address in future studies.